Environmental misinformation: challenges and impacts for digital literacy (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This work presents the main impacts of disinformation, which has primarily focused on the environmental and scientific sectors since its rise under the Bolsonaro administration. It is used to disseminate fake news and attempt to discredit data, particularly during the COVID-19 pandemic. Furthermore, it explores the concept of literacy and how literacy education can be integrated into the digital world. Fact-checking, coupled with rapidly evolving technological advances, helps society learn, through digital literacy, how to verify information and draw its own conclusions.